2010
DOI: 10.1074/jbc.m110.126821
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Generated by NADPH Oxidase 2 and 4 Are Required for Chondrogenic Differentiation

Abstract: Although generation of reactive oxygen species (ROS) by NADPH oxidases (Nox) is thought to be important for signal transduction in nonphagocytic cells, little is known of the role ROS plays in chondrogenesis. We therefore examined the possible contribution of ROS generation to chondrogenesis using both ATDC5 cells and primary chondrocytes derived from mouse embryos. The intracellular level of ROS was increased during the differentiation process, which was then blocked by treatment with the ROS scavenger N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 48 publications
6
99
0
3
Order By: Relevance
“…Some authors have suggested that constitutively active NOX4 acts as an oxygen sensor and that NOX4-mediated ROS signaling results in downstream activation of NOX1 and NOX2 and amplification of the ROS signal through recruitment of the cytosolic phox activator proteins and the Rac1 GTPase (29). Moreover, there is evidence in some cell types, such as preosteoclasts and chondrocytes, that multiple NOX enzymes can compensate for each other in the same pathway (15,33). However, in other cells, NOX4 and NOX2 appear to regulate separate pathways via different sets of MAP kinases (1).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that constitutively active NOX4 acts as an oxygen sensor and that NOX4-mediated ROS signaling results in downstream activation of NOX1 and NOX2 and amplification of the ROS signal through recruitment of the cytosolic phox activator proteins and the Rac1 GTPase (29). Moreover, there is evidence in some cell types, such as preosteoclasts and chondrocytes, that multiple NOX enzymes can compensate for each other in the same pathway (15,33). However, in other cells, NOX4 and NOX2 appear to regulate separate pathways via different sets of MAP kinases (1).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we demonstrate that WISP3 inhibits IGF1 induced collagen X induction, ROS accumulation and alkaline phosphatase activity, all of which are associated with the induction of chondrocyte hypertrophy (Böhme et al, 1992;Wang et al, 1999;Kronenberg, 2003;Zheng et al, 2003;Morita et al, 2007;Mueller and Tuan, 2008;Wu et al, 2008;Kim et al, 2010). Moreover, both IGF1 and ROS in turn stimulate WISP3 expression.…”
mentioning
confidence: 82%
“…Additional analysis of the literature suggested ATRA could also induce Sox9 at early nSMase2 induction by cyclopamine (21), was used. Cells were pretreated for 3 h with 500 M NAC prior to stimulation with ATRA for 24 h, with previous studies demonstrating this is sufficient time for NAC to exert its antioxidant effects (26,27). Results indicated that ATRA induction of nSMase2 was comparable in the presence and absence of NAC (Fig.…”
Section: Identification Of Transcription Factors Acutely Induced By Atramentioning
confidence: 99%